1998
DOI: 10.1016/s0735-1097(98)00494-x
|View full text |Cite
|
Sign up to set email alerts
|

Expression and distribution of brain natriuretic peptide in human right atria

Abstract: Expression of BNP and BNP mRNA is augmented in the atria with increased pressure, and distributed predominantly in the subendocardial side. The level of BNP mRNA was well correlated with that of ANP mRNA. Thus, these two genes might be commonly regulated in response to atrial pressure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
37
0
4

Year Published

2001
2001
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(44 citation statements)
references
References 33 publications
3
37
0
4
Order By: Relevance
“…Indeed, contradictory data are available on the regulation of ANP and BNP in the atria during the development of heart failure. Our findings support previous studies by Pemberton et al (1997) and Doyama et al (1998). The former demonstrated that the ANP:BNP mRNA ratio in the atrium was not changed after induction of CHF by rapid ventricular pacing in sheep, compared with control animals.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Indeed, contradictory data are available on the regulation of ANP and BNP in the atria during the development of heart failure. Our findings support previous studies by Pemberton et al (1997) and Doyama et al (1998). The former demonstrated that the ANP:BNP mRNA ratio in the atrium was not changed after induction of CHF by rapid ventricular pacing in sheep, compared with control animals.…”
Section: Discussionsupporting
confidence: 92%
“…The former demonstrated that the ANP:BNP mRNA ratio in the atrium was not changed after induction of CHF by rapid ventricular pacing in sheep, compared with control animals. Similar observations were reported by Doyama et al (1998), who examined the expression of these peptides by Northern blotting analysis in the right atria of patients undergoing cardiac surgery. Their findings suggest that ANP and BNP share a common regulatory mechanism and that their synthesis may be commonly associated with atrial stretch.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…BNP mRNA is expressed in atrial muscle, where BNP is also secreted; both have been reported to increase by atrial fibrillation and hypertrophy (24,(29)(30)(31)(32). Although the kinetics of atrial-derived BNP in heart failure are not fully known, some studies (23)(24)(25) propose that the atrium is the major source of secretion in the early stage of lowered cardiac function, and that BNP levels from the ventricle increase after the progression to heart failure.…”
Section: Discussionmentioning
confidence: 99%
“…Under normal circumstances the myocytes in the atria and the ventricles in the human heart will produce ANP to regulate fluid homeostasis [8,9] but when the ventricles and atria in the heart are stretched, the synthesis of these peptides increases. ANP gene expression is increased in the ventricular myocardium of the failing heart proportionally with the severity of congestive heart failure or ventricular haemodynamic overload [10]. Therefore resting levels of natriuretic peptides are higher in chronic heart failure and atrial fibrillation compared with normal [1,11,12].…”
Section: Introductionmentioning
confidence: 99%